2012
DOI: 10.1175/jcli-d-11-00070.1
|View full text |Cite
|
Sign up to set email alerts
|

Interdecadal Variations in ENSO Teleconnection to the Indo–Western Pacific for 1870–2007

Abstract: Slow modulation of interannual variability and its relationship to El Niñ o-Southern Oscillation (ENSO) isinvestigated for the period of 1870-2007 using shipboard surface meteorological observations along a frequently traveled track across the north Indian Ocean (NIO; from the Gulf of Aden through Malacca Strait) and the South China Sea (to Luzon Strait). During the decades in the late nineteenth-early twentieth century and in the late twentieth century, the El Niñ o-induced NIO warming persists longer than du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
87
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 84 publications
(119 reference statements)
3
87
0
Order By: Relevance
“…In this case, the distinct effects of the different background state on the equatorward wave rays are responsible for this asymmetry. Under the CP El Niño-type background state, the equatorward wave rays tend to be reflected at the latitudes where the zonal wind equals zero (U = 0), and then successfully captured 1 3 regression, are usually employed by most of the studies (e.g., Chowdary et al 2012;Wang et al 2008a;Wu et al 2003;among others). Actually, climate responses to ENSO are not simply opposite, but show an apparent nonlinearity between the warm and cold phases (Zhang et al 2014a(Zhang et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the distinct effects of the different background state on the equatorward wave rays are responsible for this asymmetry. Under the CP El Niño-type background state, the equatorward wave rays tend to be reflected at the latitudes where the zonal wind equals zero (U = 0), and then successfully captured 1 3 regression, are usually employed by most of the studies (e.g., Chowdary et al 2012;Wang et al 2008a;Wu et al 2003;among others). Actually, climate responses to ENSO are not simply opposite, but show an apparent nonlinearity between the warm and cold phases (Zhang et al 2014a(Zhang et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found significant warming and changes in the Indian Ocean SST during recent few decades based on observation (Abram et al 2008;Alory et al 2007;Chowdary et al 2012;Ihara et al 2008). Ihara et al (2008) showed that the western equatorial Indian Ocean warms more than the eastern counterpart during recent decades; the mean SST gradient across the equatorial Indian Ocean is anomalously positive to the west reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The long-term IOB SST warming has commonly been attributed to the anthropogenic effect associated with global warming [Barnett et al, 2005;Pierce et al, 2006]. Nevertheless, decadal changes over the Indian Ocean have been found closely related to ENSO [Cole et al, 2000;Allan et al, 1995;Reason et al, 2000;Xie et al, 2010;Chowdary et al, 2012]. For example, Allan et al [1995] suggested that the epochal changes in the mean condition over the south Indian Ocean are in-phase with ENSO-related correlation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Allan et al [1995] suggested that the epochal changes in the mean condition over the south Indian Ocean are in-phase with ENSO-related correlation patterns. Chowdary et al [2012] showed the epochal change in the persistency of the El Niño-induced warmer SST anomalies over the north Indian Ocean. This study will examine the interdecadal variation of the basinwide SST in the Indian Ocean and provide evidence to show that, during the past 140 years, the most significant interdecadal IOB warming exists around 1970s, and it is intimately related to decadal changes of ENSO since 1970s.…”
Section: Introductionmentioning
confidence: 99%